Reestablishment of Rhipicephalus secundus Feldman-Muhsam, 1952 (Acari: Ixodidae) - Mumcuoglu, Kosta Y.; Estrada-Peña, Agustín; Tarragona, Evelina Luisa; Sebastian, Patrick Stephan; Guglielmone, Alberto; Nava, Santiago (Elsevier, 2022)
Rhipicephalus secundus is reestablished as a valid tick name within the Rhipicephalus sanguineus group and removed from the synonymy list of Rhipicephalus turanicus. Morphological re-description of both male and female of R. secundus and the analysis of its phylogenetic position based on mitochondrial DNA sequences are presented. The morphological re-description was made with tick specimens collected on goat in Israel. The phylogenetic analyses showed that R. secundus belong to a different clade from those formed by R. turanicus sensu stricto (s.s.) and R sanguineus s.s., and by other taxa from the R. sanguineus group. Rhipicephalus secundus is morphologically related to R. turanicus, but the scutal punctation pattern of both male and female allows the morphological differentiation between R. secundus and R. turanicus, punctations being clearly more numerous and larger in the latter. Both male and female of R. secundus can be differentiated from those of R. sanguineus s.s. by the shape of the spiracular plate. In males, the dorsal prolongation of the spiracular plate is equal to the breadth of the adjacent festoon in R. secundus, while it is narrower than the breadth of the adjacent festoon in R. sanguineus s.s. The dorsal prolongation of the spiracular plate in the female of R. secundus is wider than in the female of R. sanguineus s.s. The genital apertures of the females of R. secundus and R. sanguineus are both U-shaped, but in R. sanguineus s.s. it is broader than in R. secundus. Considering the results obtained in this study, it can be stated that R. secundus is present at least in Israel, Palestinian Territories, Turkey, Albania and southern Italy, but it is necessary to carry out additional studies to determine the geographical range and host usage of this species.